(untitled) (مجلة الواحات للبحوث والدراسات, 2016)
The milk-weed family (Asclepiadaceae) is very rich in latex and a number of species have been investigated for the constituents of solvent extractables (Adams et al.1983) andPergulariatomentosa.Lis plant belonging to the milkweed family